Role of Notaries and PPAT in Overcoming Land Mafia Problems - Ines Lovitya Trisnanti; Ninda Fatmawati (Budapest International Research and Critics University, 2022)
Several cases due to the existence of the land mafia that often occur at this time have become a serious concern for the government. Given the importance of land for the community, certainty, order, and legal protection demand that legal traffic in people's lives requires legal evidence, so that people get legal certainty over their ownership. To determine the status of ownership of a plot of land, it must involve a Notary PPAT officer administratively. This study aims to examine the practices of the land mafia and the parties who must be involved in the practice of land mafia crimes as well as the role of Notaries and PPAT in overcoming the problem of land mafia.The research method used in this research is normative legal research with a literature review approach to laws and regulations related to the focus of research on land mafia.PPAT Notaries have a central and strategic role in eradicating, overcoming and preventing the occurrence of land mafia. One of the roles that must be carried out by PPAT Notaries is to really pay attention to the regulatory system for making land deeds, ensuring the originality of documents by confirming to the parties concerned, and ensuring that interested parties actually come face to face with the PPAT Notaries. when making the deed.